2019
DOI: 10.1080/15710882.2019.1631349
|View full text |Cite
|
Sign up to set email alerts
|

Socio-materiality of trust: co-design with a resource limited community organisation

Abstract: Trust is an essential if often implicit aspect of co-design particularly when working in community-based, political and sensitive settings. Current co-design literature, however, remains fairly limited focusing on interactions between people as primary agents of trust. Drawing on research conducted with a poverty alleviation charity based in the UK, we illustrate how trust and distrust can also be mediated through material resources used in the codesign process. The paper highlights the significance of materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…In line with previous research (Birendra et al, 2019; Clarke et al, 2019) and the conceptualization of SDL and SET (Cropanzano & Mitchell, 2005; Vargo & Lusch, 2016), this study revealed a reciprocal effect of trust in value co-creation for hospitality customers. Specifically, our results showed that customer trust in the service provider may serve as an antecedent of value co-creation processes, supporting the premise by Abela and Murphy (2008); as well as a relational outcome (Shulga et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous research (Birendra et al, 2019; Clarke et al, 2019) and the conceptualization of SDL and SET (Cropanzano & Mitchell, 2005; Vargo & Lusch, 2016), this study revealed a reciprocal effect of trust in value co-creation for hospitality customers. Specifically, our results showed that customer trust in the service provider may serve as an antecedent of value co-creation processes, supporting the premise by Abela and Murphy (2008); as well as a relational outcome (Shulga et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Mazzella et al (2016) identified trust as a fundamental component for creating a sustainable environment for collaboration. Although highly relevant as a relational networked concept for value co-creation (Clarke et al, 2019), reciprocity of trust, its constraints, rules, and characteristics received limited attention. To date, hospitality research has provided little evidence of how trust influences value co-creation or how the brand is influenced by the process, specifically in co-creation contests (Shulga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the findings of previous research (Bratteteig, Bødker, Dittrich, Mogensen, & Simonsen, 2012;Clarke et al, 2019;Pirinen, 2016;Warwick, 2017), mutual trust among members of the same organisation and among project partners at all levels, from government to community, is considered valuable in collaborative design practice. In the participants' words, trust is "the core of everything we do" (Anne) and "[t]here should be a certain amount of trust before we even start the work" (Thomas).…”
Section: Mutual Trustsupporting
confidence: 78%
“…The novelty of the technologies that we witnessed within this study did, perhaps surprisingly, not venture beyond that of a smartphone (to scroll through) or a WhatsApp social media group -arguably resulting in descriptions of mundane technologies [26]. Although we focused our attention on a detailed look into a single-third sector organisation, we believe that based on the corpus of other work on this topic [16,49], our study does represent an accurate picture of the practices involved by a technically-illiterate and resourcepoor third-sector context in the context of UK austerity. We do not believe that the lack of or use of simplistic technologies is something to deter motivated designers, however, as Strohmayer et al writes "small changes to the materiality of mundane technologies" can generate an enormously positive impact to those reliant on those technologies, particularly those groups excluded from mainstream design [70].…”
Section: Embrace and Account For The Mundanementioning
confidence: 95%
“…As we did not focus our data collection on non-technical tools in this context, we regrettably cannot contrast the impact of a change in service material or the absence of technology with a robust evidencebase. Indeed, this process required a lengthy and emotionally intensive investment of trust, time and resource for both the lead author and <Safe Start>, which some organisations would not be able to offer so readily [9,16]. As such, we recommend researchers consider an engaged approach that seeks to involve both front-line and managerial staff handling perpetrators of domestic violence [29].…”
Section: Critical Reflection and Limitationsmentioning
confidence: 99%